2007
DOI: 10.1007/s11606-007-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemic Encephalopathy Caused by Carnitine Deficiency

Abstract: Carnitine is an essential co-factor in fatty acid metabolism. Carnitine deficiency can impair fatty acid oxidation, rarely leading to hyperammonemia and encephalopathy. We present the case of a 35-year-old woman who developed acute mental status changes, asterixis, and diffuse muscle weakness. Her ammonia level was elevated at 276 microg/dL. Traditional ammonia-reducing therapies were initiated, but proved ineffective. Pharmacologic, microbial, and autoimmune causes for the hyperammonemia were excluded. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 33 publications
(45 reference statements)
1
37
1
2
Order By: Relevance
“…Treatment with L-carnitine ameliorated symptoms of encephalopathy subsequent to long term use of valproate [79], and the antibiotic cefditoren pivoxil [80]. Case reports indicate that improvement with L-carnitine treatment was also seen in hyperammonemic encephalopathy caused by carnitine deficiency that manifested several years after gastrointestinal bypass surgery [83] and in encephalopathy secondary to gluten enteropathy [84]. Additionally, a randomized clinical trial reported some improvement in Friedreich’s ataxia patients treated with L-carnitine [85].…”
Section: Neuroprotection Afforded By L-carnitine Supplementation In Pmentioning
confidence: 99%
“…Treatment with L-carnitine ameliorated symptoms of encephalopathy subsequent to long term use of valproate [79], and the antibiotic cefditoren pivoxil [80]. Case reports indicate that improvement with L-carnitine treatment was also seen in hyperammonemic encephalopathy caused by carnitine deficiency that manifested several years after gastrointestinal bypass surgery [83] and in encephalopathy secondary to gluten enteropathy [84]. Additionally, a randomized clinical trial reported some improvement in Friedreich’s ataxia patients treated with L-carnitine [85].…”
Section: Neuroprotection Afforded By L-carnitine Supplementation In Pmentioning
confidence: 99%
“…In primary systemic carnitine deficiency, an autosomal recessive condition, the organic cation transporter gene OCTN2 is mutated, resulting in hypocarnitinemia secondary to reduced renal tubular reabsorption of carnitine. Patients with this often present with hyperammonemia, encephalopathy, hypoglycemia, and myopathies [72].…”
Section: Drug Related Causesmentioning
confidence: 99%
“…[7][8][9] Carnitine deficiency alone has been documented to cause encephalopathy, 10 and, therefore, administration of valproate in these patients could further reduce levels of carnitine, predisposing them to encephalopathy. [7][8][9] Carnitine deficiency alone has been documented to cause encephalopathy, 10 and, therefore, administration of valproate in these patients could further reduce levels of carnitine, predisposing them to encephalopathy.…”
Section: Discussionmentioning
confidence: 99%